Turning the Tide on Poverty: Community climate in economically distressed rural communities. Issue 3 (26th May 2016) - Tyler-Mackey, Crystal; Monroe, Pamela A.; Dyk, Patricia Hyjer; Welborn, Rachel; Worthy, Sheri Lokken
Abstract: Qualitative research analysis uncovered themes across the multiple rural, economically distressed communities that participated in the Turning the Tide on Poverty project. Community climate, referred to as the perception of the community by its members, was one theme that emerged. Intertwined with this theme is a discussion regarding race relations. How people felt about their community may have influenced whether or not the Turning the Tide on Poverty project was launched, implemented, and/or sustained in communities. To further examine the community climate theme, key questions were developed: What is the sense, perception, or tone of the community? How do respondents describe their community and its chance for a positive future? Did the community embrace Tide and the community projects? The Tide research team also examined how the community handled disagreements and difficult topics as the context for attempts to encourage more positive civic discourse.